Cellular Proliferation of Equine Bone Marrow- and Adipose Tissue-Derived Mesenchymal Stem Cells Decline With Increasing Donor Age - Bagge, Jasmin; MacLeod, James N.; Berg, Lise C. (Frontiers in Veterinary Science, 2020)
Background: Bone marrow (BM)- and adipose tissue (AT) derived mesenchymal stem cells (MSCs) are used increasingly for autologous cell therapy in equine practice to treat musculoskeletal and other injuries. Current recommendations often call for 10-100 million MSCs per treatment, necessitating the expansion of primary cells in culture prior to therapeutic use. Of concern, human and rodent studies have shown a decline of both MSC recovery from sampled tissue and in vitro proliferative capacity with increasing donor age. This may be problematic for applications of autologous cell-based therapies in the important equine demographic of older patients. Objectives: To investigate the effect of donor age on the cellular proliferation of equine BM- and AT-MSCs. Study design: In vitro study. Methods: BM- and AT-MSCs and dermal fibroblasts (biological control) were harvested from horses in five different age groups (n=4, N=60); newborn (0 days), yearling (15-17 months), adult (5-8 years), middle-aged (12-18 years), and geriatric (≥22 years). Proliferation of the cells was tested using an EdU incorporation assay and steady state mRNA levels measured for targeted proliferation, aging, and senescence biomarkers. Results: The cellular proliferation of equine BM- and AT-MSCs declined significantly in the geriatric cohort relative to the younger age groups. Proliferation levels in the two MSC types were equally affected by donor age. Analysis of steady state mRNA levels showed an up-regulation in tumor suppressors, apoptotic genes, and multiple growth factors in MSCs from old horses, and a down-regulation of some pro-cycling genes with a few differences between cell types. Main limitations: Potential age-dependent differences in cell function parameters relevant to cell-therapy application were not investigated. Conclusions: The cellular proliferation of equine BM- and AT-MSCs declined at advanced donor ages. High levels of in vitro proliferation were observed in both MSC types from horses in the age groups below 18 years of age.